Upaya Guru dalam Meningkatkan Kualitas Membaca Al-Quran - Erianti, Soli; Arifah, Umi (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The research objectives are: To determine the efforts of TPQ teachers in improving the quality of Al-Quran reading in the Al-Quran Al-Hikmah Education Park, Bandung Village, Kebumen. This research is in the form of qualitative research. The informants in this research were the head of TPQ, Ustadz/Ustadzah TPQ, and Santri TPQ. Data collection techniques use observation, interviews and documentation. The data analysis techniques used are data reduction, data display, and drawing conclusions. There are several ways for teachers to improve the quality of reading the Koran at the Al-Quran Al-Hikmah Education Park, Bandung Kebumen Village, namely teachers identify student characteristics by frequently communicating with students and observing how students interact with their friends. Teachers provide equal learning opportunities to students by preparing steps before learning, using methods in learning, and using media in the teaching and learning process. The steps taken are to get students used to sitting neatly first, the method used is the Qiraati method, and the media used in the learning process is a large book as a substitute for a blackboard. And the teacher's next effort is that the teacher helps develop potential and overcome student deficiencies by monitoring students' personal development, providing guidance, and motivating students.